The moral-spiritual value preferences of teachers of the public secondary schools of Manila - Vivar, Teofista L. 1930- (s.n.], 1971)
This study determined the value preferences of public secondary schools of Manila. The instrument used was the value scale prepared by the National Council for the Study and Development of the Filipino Children and Youth. Analysis of the results revealed the hierarchy of the moral-spiritual values of the teachers which is as follows: moral equality, devotion to truth, moral responsibility, respect for human personality, brotherhood, respect for excellence, pursuit of happiness, and spiritual enrichment.